Contrastive independent component analysis for salient patterns and dimensionality reduction - Kexin Wang; Aida Maraj; Anna Seigal (Proceedings of the National Academy of Sciences, 2025)
In recent years, there has been growing interest in jointly analyzing a foreground dataset, representing an experimental group, and a background dataset, representing a control group. The goal of such contrastive investigations is to identify salient features in the experimental group relative to the control. Independent component analysis (ICA) is a powerful tool for learning independent patterns in a dataset. We generalize it to contrastive ICA (cICA). For this purpose, we devise a linear algebra–based tensor decomposition algorithm, which is more expressive but just as efficient and identifiable as other linear algebra–based algorithms. We establish the identifiability of cICA and demonstrate its performance in finding patterns and visualizing data, using synthetic, semisynthetic, and real-world datasets, comparing the approach to existing methods.